Hadith on Moral Education: Critical Ethics for the Young Generation in the Era of Disruption - St. Maemunah; La Ode Ismail Ahmad; Abdul Rahman Sakka (al-Afkar, Journal For Islamic Studies, 2026)
The era of disruption has brought significant changes to social and cultural life, particularly through the development of digital technology, which influences the mindset and behavior of the younger generation. Widespread access to information, on the one hand, provides opportunities for self-development, but on the other, it also presents challenges in the form of the rise of negative values such as individualism, instant gratification, and a decline in ethical standards. This situation demands strengthening moral education that can foster critical thinking and integrity. This study aims to analyze the moral values in the hadith and their relevance to the moral education of the younger generation in the era of disruption. The method used is an analysis of four hadith related to the values of honesty, empathy, brotherhood, gratitude, and patience, through the takhrij approach, classification, and interpretation of the hadith. The results show that all the hadith studied are considered authentic and contain universal moral principles relevant to building the character of the younger generation. These values include careful distinction between what is permissible and what is forbidden, the importance of honesty and brotherhood, empathy for others, and gratitude and patience in facing life. Implementing hadith-based moral education can be a solution to address the moral crisis in the modern era, as it not only instills ethical values but also fosters critical thinking skills. Thus, hadith-based moral education plays a crucial role in shaping a young generation with morals, resilience, and the ability to adapt wisely to changing times.